2016
DOI: 10.3390/ijms17111813
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of Dunaliella salina Ds-26-16 and Salt-Tolerant Response in Escherichia coli

Abstract: Identification and evolution of salt tolerant genes are crucial steps in developing salt tolerant crops or microorganisms using biotechnology. Ds-26-16, a salt tolerant gene that was isolated from Dunaliella salina, encodes a transcription factor that can confer salt tolerance to a number of organisms including Escherichia coli (E. coli), Haematococcus pluvialis and tobacco. To further improve its salt tolerance, a random mutagenesis library was constructed using deoxyinosine triphosphate-mediated error-prone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…They have reduced levels of lysine and cysteine residues, and a higher content of aspartate and small hydrophobic residues. Structurally, they contain higher amounts of random coil structure at the expense of α-helix [145][146][147][148][149][150]. A recent report from Warden et al demonstrated that the extended binding of cations by acidic residues with complementary chelating partners and interactions through the highly ordered hydration shells of the cations are primary mechanisms of halotolerance [145].…”
Section: Engineering Cellulases For Enhanced Thermostabilitymentioning
confidence: 99%
“…They have reduced levels of lysine and cysteine residues, and a higher content of aspartate and small hydrophobic residues. Structurally, they contain higher amounts of random coil structure at the expense of α-helix [145][146][147][148][149][150]. A recent report from Warden et al demonstrated that the extended binding of cations by acidic residues with complementary chelating partners and interactions through the highly ordered hydration shells of the cations are primary mechanisms of halotolerance [145].…”
Section: Engineering Cellulases For Enhanced Thermostabilitymentioning
confidence: 99%